Variation of lycopene and beta-carotene contents after harvesting of gac fruit and its prediction - Bhumsaidon, Apinya; Chamchong, Montip (Agriculture and Natural Resources, 2016)
The effects were investigated of three different stages of harvesting, the storage time and sample preparation methods before extraction using a Waring blender (WBM) or ball mill (BMM) on the lycopene and b-carotene contents from the gac aril. It was found that after harvesting and being stored at 26 ± 1 oC and 24 ± 1% RH for 15 d, the lycopene contents from the color break, medium ripe and fully ripe stages of gac fruits grown in Thailand were in the ranges 0.11-8.99 mg/100 g fresh weight (FW), 3.88-22.94 mg/100 g FW and 18.95-50.11 mg/100 g FW, respectively, while the b-carotene contents were in the ranges 0.002-4.82 mg/100 g FW, 0.31-13.59 mg/100 g FW and 22.68-39.16 mg/100 g FW, respectively. In addition, neither the WBM nor the BMM sample preparation method had any significant (p > 0.05) effect on the analysis of these phytonutrients. Gac fruit at the fully ripe stage after 6 d of storage provided the highest lycopene content of 50.11 ± 1.59 mg/100 g FW, while the b-carotene was found highest (39.16 ± 1.29 mg/100 g FW) from fully ripe stage fruit after 15 d storage or when they had spoiled. Without classifying the fruits according to harvesting stages, equations for mixed ripe fruit were able to predict the lycopene and b-carotene contents in the aril with coefficients of determination of 0.77 and 0.89 with standard errors of the estimate of 16.09 and 6.39, respectively.